Spermicidal effects of lemon juice and juices from other natural products - Suthutvoravut, Somsak; Kamyarat, Ourawan (My University, 2016)
The study of spermicidal effects of lemon juice and juices from other natural products consisting of pineapple juice, apple juice and aloe vera juice, was carried out to develop methods of contraception using natural products. Semen was donated by 20 men from infertile couples who came to an infertility clinic at the Department of Obstetrics and Gynecology, Ramathibodi Hospital, Bangkok, Thailand from 1 November 2007 to 31 March 2010. Spermicidal effects were measured by observing changes in sperm viability, morphology and motility after the semen was mixed with lemon juice and the juices from the other natural products (pineapple juice, apple juice and aloe vera juice). Changes in sperm characteristics were compared with pure semen left at room temperature. After the semen was mixed with lemon juice, sperm were instantaneously immobilized and irreversibly deformed. A reduced spermicidal effect was observed when the semen was mixed with the other juices. A second, profound spermicidal effect was observed when semen was mixed with pineapple juice. The least effects were observed when the semen was mixed with aloe vera juice. This information can be used for the further development of natural barrier methods of contraception.
Keywords: Lemon juice; Natural products; Spermicide